Peran Pendidikan Kewarganegaraan Sebagai Pendidikan Multikultural dalam Menanggulangi Radikalisme - Pipit Widiatmaka; Arief Adi Purwoko; Oki Anggara; Putri Handayani Lubis (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to determine the meaning of radicalism, the role of civic education in universities, and the role of civic education as a vehicle for multicultural education to anticipate the development of radicalism in universities. The type of research used is qualitative and uses library research methods. Data collection techniques using document studies and data analysis used content analysis. The results of the study indicate that radicalism is an ideology that is very threatening to the diversity that exists in Indonesia, until now this ideology has begun to develop in the world of education, especially in universities. Radicalism began to develop in universities because most of the students were colleges were gathering places for young people and were easily influenced by something new. The role of civic education in higher education is very important and much needed, considering that this course is personality development and moral education. Citizenship education can function as multicultural education so that these courses can open students' insight that Indonesia is a multicultural country and can depend on all existing differences so that radicalism in higher education can be overcome. Through civic education, it can also build the character of tolerance, through an effective learning process with character education strategies, namely moral knowing, moral loving, and moral doing. Educators at universities must supervise their students' activities in the university environment.